2016
DOI: 10.1111/apa.13620
|View full text |Cite
|
Sign up to set email alerts
|

Physician‐assisted dying for children is conceivable for most Dutch paediatricians, irrespective of the patient's age or competence to decide

Abstract: Most Dutch paediatricians felt PAD was conceivable, even under the age of 12 if requested by the parents. They seemed driven by a sense of duty to relieve suffering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 24 publications
0
13
1
1
Order By: Relevance
“…Furthermore, in a study investigating physicians’ opinions about EAS for children, GPs and medical specialists less often agreed with the idea of granting EAS for a child without parental consent than pediatricians [ 85 ]. Diverging opinions among pediatricians on the extent to which parents should be involved in EAS decision-making for children were found in other studies as well [ 73 , 86 ].…”
Section: Resultsmentioning
confidence: 78%
See 4 more Smart Citations
“…Furthermore, in a study investigating physicians’ opinions about EAS for children, GPs and medical specialists less often agreed with the idea of granting EAS for a child without parental consent than pediatricians [ 85 ]. Diverging opinions among pediatricians on the extent to which parents should be involved in EAS decision-making for children were found in other studies as well [ 73 , 86 ].…”
Section: Resultsmentioning
confidence: 78%
“… death certificate study and questionnaires Death certificates, attending physicians (n = 6860) Buiting et al [ 76 ] 2011 To investigate how good SCEN consultations differ from less satisfactory SCEN consultations questionnaires and qualitative interviews questionnaires: euthanasia consultants ( n = 594) Interviews: euthanasia consultants (n = 14), physicians who had requested an euthanasia consultation (n = 12), relatives (n = 10) De Boer et al [ 71 ] 2011 To gain insight into how ADs for euthanasia affect resident care in nursing homes questionnaires and in-depth interviews questionnaires: elderly care physicians ( n = 434) Interviews: elderly care physicians (n = 11) and relatives (n = 8) of deceased dementia patients with euthanasia AD Van Delden et al [ 42 ] 2011 To investigate knowledge, opinions and experiences regarding euthanasia, palliative sedation and ADs among health care professionals and members of the general public. questionnaires and in-depth interviews questionnaires: members of the general public ( n = 1960), physicians ( n = 793), nurses ( n = 1243) Interviews: physicians ( n = 49), nurses (n = 18), members of the general public ( n = 16) Van der Heide et al [ 47 ] 2012 To examine the practice of medical decisions at the end of life after 10 years of the Euthanasia Act, how the regulations of the Euthanasia Act are applied and which problems occur questionnaires and in-depth interviews questionnaires: physicians ( n = 2000) interviews : physicians (n = 30, 22/30 GPs), relatives of patients who died of EAS ( n = 25) Onwuteaka-Philipsen et al [ 7 ] 2017 To determine whether the Euthanasia Act reaches its aims survey and in-depth interviews questionnaires: physicians ( n = 2500), members of the general public ( n = 2500) interviews : psychiatrists ( n = 17) Bolt et al [ 73 ] 2017 To explore the situations in which pediatricians found PAD conceivable and to describe the roles of the patient and parents, the patient’s age and their life expectancy survey and in-depth interviews pediatricians ( n = 276 and n = 8) ...…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations